Ácidos politiónicos: efectos sobre los aceros al carbono - Duffó, Gustavo Sergio; Garavaglia, Ricardo N. (Comisión Nacional de Energía Atómica; Argentina, 1985)
Fil: Duffó, Gustavo Sergio Comisión Nacional de Energía Atómica; Argentina